Garlic consumption and colorectal cancer risk in man: a systematic review and meta-analysis. Issue 2 (6th May 2015) - Chiavarini, Manuela; Minelli, Liliana; Fabiani, Roberto
Abstract: Objective: Colorectal cancer shows large incidence variations worldwide that have been attributed to different dietary factors. We conducted a meta-analysis on the relationship between garlic consumption and colorectal cancer risk. Design: We systematically reviewed publications obtained by searching ISI Web of Knowledge, MEDLINE and EMBASE literature databases. We extracted the risk estimate of the highest and the lowest reported categories of intake from each study and conducted meta-analysis using a random-effects model. Results: The pooled analysis of all fourteen studies, seven cohort and seven case–control, indicated that garlic consumption was not associated with colorectal cancer risk (OR=0·93; 95 % CI 0·82, 1·06, P =0·281; I 2 =83·6 %, P ≤0·001). Separate analyses on the basis of cancer sites and sex also revealed no statistically significant effects on cancer risk. However, when separately analysed on the basis of study type, we found that garlic was associated with an approximately 37 % reduction in colorectal cancer risk in the case–control studies (combined risk estimate=0·63, 95 % CI 0·48, 0·82, P =0·001; I 2 =75·6 %, P ≤0·001). Conclusions: Our results suggest that consumption of garlic is not associated with a reduced colorectal cancer risk. Further investigations are necessary to clarify the discrepancy between results obtained from different types of epidemiological studies.